2021
DOI: 10.33581/2520-2243-2021-1-90-101
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of lattice fluid with SALR-potential on a simple square lattice

Abstract: The transport properties of the lattice fluid with the attraction interaction between the nearest and repulsion interaction between the next-next-nearest neighbours on the square lattice are investigated. Computer simulation by the Monte Carlo method of the diffusion process in the specified system has been realised. The jump and tracer diffusion coefficients were determined. The dependence of the diffusion coefficients versus the concentration of adparticles and the interaction parameter of the model is inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The phase diagram of the system is shown in figure 5. The phase diagram turns out to be much narrower compared to the system with attractive interaction [33]. In general, it can be noted that the thermodynamic characteristics do not qualitatively reveal the new properties in comparison with a similar system with the attraction of the nearest neighbors.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…The phase diagram of the system is shown in figure 5. The phase diagram turns out to be much narrower compared to the system with attractive interaction [33]. In general, it can be noted that the thermodynamic characteristics do not qualitatively reveal the new properties in comparison with a similar system with the attraction of the nearest neighbors.…”
Section: Resultsmentioning
confidence: 75%
“…Comparison of the results of analytical calculations and modelling showed that the parameter 𝜆 included in relation (4.2), which ensures the equality of the critical parameters of the system found during its modelling and calculated within the framework of the diagram approximation, is equal to 1.10308. It can be noted that its value differs very insignificantly from the analogous value obtained for a system with attraction between nearest neighbors [33]. The isotherms of the chemical potential calculated for temperatures above and below the critical temperature 𝑇 𝑐 are show in figure 3.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations